Physical Activity and Arterial Stiffness: A Narrative Review - Jinyu Yang; Xiaoqian Chen; Xiang Chen; Lihua Li (The Journal of Clinical Hypertension)
ABSTRACT Arterial stiffness is a significant predictor of cardiovascular disease and mortality. Physical activity (PA) has been extensively studied for its potential to reduce arterial stiffness, but the relationship between different types, durations, and intensities of PA and arterial stiffness remains a topic of ongoing research. Therefore, in this narrative review, we evaluated the current evidence focusing on the effect of PA on arterial stiffness and vascular health and discussed the known underlying physiological mechanisms. PA, irrespective of its intensity or pattern, is consistently associated with lower arterial stiffness. Aerobic exercise, particularly at higher intensities, is the most effective strategy for reducing arterial stiffness. These benefits are especially significant in populations with higher cardiovascular risk, such as those with type 2 diabetes mellitus and hypertension. Therefore, maintaining an active lifestyle into older age is crucial for vascular health and may contribute to healthy aging.